Barrier contraception methods. Issue 6 (June 2019) - Kendall, Emily; Lebari, Dornubari
Barrier contraceptive methods are the oldest type of reversible contraception still available. They work by preventing the egg and the sperm coming into contact with one another, thereby preventing fertilisation. Some barrier contraceptive methods have the added benefit of preventing transmission of sexual infections. The main types of barrier contraceptives are the male and female condoms, diaphragms and cervical caps. This article aims to provide an overview of the different barrier methods for contraception, their efficacy, and advantages and disadvantages.